Cardiac and renal biomarkers in recreational runners following a 21 km treadmill run. Issue 12 (3rd September 2020) - Yeo, Tee Joo; Ling, Lieng H.; Lam, Carolyn Su Ping; Chong, Jenny Pek Ching; Liew, Oi Wah; Teo, Zhen Long; Gong, Lingli; Richards, Arthur Mark; Chan, Mark Y.
Abstract: Background: Highly trained athletes running 42 km or more demonstrate elevated cardiac biomarkers, ventricular dysfunction, and decreased glomerular filtration rate (GFR). Whether similar changes occur in the much larger population of recreational runners following half‐marathon distance running is unclear. Hypothesis: Recreational runners exhibit changes in myocardial and renal biomarkers, including ventricular strain, after a half‐marathon treadmill run. Methods: 10 recreational subjects (mean age 36.5 ± 6.5 years) ran 21 km on a treadmill (mean completion time 121.6 ± 16.1 minutes). Serum high‐sensitivity troponin T (hsTnT), amino‐terminal pro‐brain natriuretic peptide (NT‐proBNP), creatinine, and neutrophil gelatinase‐associated lipocalin (NGAL) were measured prior to, 1 hour post‐, and 24 hours post‐exercise. Pre‐ and post‐exercise echocardiograms were performed. Results: All biomarkers increased 1 hour post‐exercise: hsTnT by 8.5 ± 8.5 pg/ml ( P < .05), NT‐ProBNP by 26.2 ± 22.8 pg/ml ( P < .05) and NGAL by 29.5 ± 37.7 ng/ml ( P =NS). By 24 hours post‐run, these biomarkers declined toward baseline levels. Right ventricle (RV) free wall and left ventricle global longitudinal strain decreased by 5.5% and 1.8%, respectively ( P < .001). Changes in NGAL correlated well with changes in serum creatinine (R = 0.79, P < .01) and GFR (R = −0.73, P < .05). Faster 21 km completion times, and a larger reduction in post‐exercise RV strain, were associated with higher NGAL levels: (R = −0.75, P = .01) and (R = 0.66, P < .05), respectively. Conclusion: A 21 km run in recreational runners is associated with transient ventricular stunning and reversible changes in myocardial and renal biomarkers. Whether repeated bouts of similar activity contributes to chronic cardiac or kidney dysfunction deserves further evaluation.